2007
DOI: 10.1002/app.25824
|View full text |Cite
|
Sign up to set email alerts
|

Polymer modified grass fiber, part 1: Characterization of grass fiber and assessment of properties of polymer modified fiber

Abstract: Natural fibers are used for reinforcement of ecofriendly green composites. These grass fibers have wide range of applications for the preparation of various domestic goods and handicraft items. But the chemical composition of the grass fiber has not been reported; therefore composition analysis of grass fiber was carried out. Morphology of the dry grass was studied by using scanning electron microscopy. Since the grass fiber contains around 22% water-soluble matters, we have studied its influence on the tensil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…Thus, more crystalline and heat resistant cellulose molecules are left over after alkali treatment. Similar results were also reported by Debasish et al17…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, more crystalline and heat resistant cellulose molecules are left over after alkali treatment. Similar results were also reported by Debasish et al17…”
Section: Resultssupporting
confidence: 92%
“…The effect of alkali treatment on the crystallinity of cellulosic materials has been investigated by various researchers. Marianne Le et al17 reported that alkali treatment hydrolyses the amorphous parts of cellulose present in fibers and treated material contains more crystalline cellulose. This is due to formation of Cell O‐Na + structure after the treatment and Na + ions come to fit in the unit cell of cellulose 18.…”
Section: Resultsmentioning
confidence: 99%
“…These probably due to the inclusion of rigid and hard rattan into soft rubber matrix which tends to immobilize the movement of macromolecular rubber chains. The more rattan is added, the more restriction in mobility is experienced by the rubber chains and as a result natural rubber composites become harder and stiffer 16–20. Besides, Costa et al8 reported that this phenomenon leads to difficulties in mixing.…”
Section: Resultsmentioning
confidence: 99%
“…The elasticity of composites is reduced resulting in more stiff and rigid composites. This leads to lower resistance to break 6, 8, 17–18, 20. M 100 and M 300 increased while elongation at break reduced further as silane CA added into the composites.…”
Section: Resultsmentioning
confidence: 99%
“…Here, the addition of SPC increased the mechanical properties of the composites. Effects of bonding agents on the curing characteristics and mechanical properties of alkali‐treated grass/NR composites have been studied by Debasish et al [16]. Thomas and coworkers [17, 18] showed that short coir, sisal, and banana fiber can be used as reinforcement for NR, polypropylene, and thermoset resins.…”
Section: Introductionmentioning
confidence: 99%